2021
DOI: 10.5624/isd.20200323
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of anterior maxillary and mandibular alveolar parameters in African American and Caucasian women: A retrospective pilot study

Abstract: Purpose The primary objective of this study was to analyze the thickness and height of alveolar bone around the maxillary and mandibular incisors. Additionally, this study aimed to compare bone parameters between Caucasian (CC) and African American (AA) female patients. Materials and Methods In this retrospective pilot study, 50 female subjects (25 CC and 25 AA) were included. The inclusion criteria were AA or CC women between the ages of 18 and 50 with a normo-divergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
2
2
0
2
Order By: Relevance
“…One study reported a significant difference in alveolar ridge thickness between the African Americans and Caucasians, with the former exhibiting thinner ridges at the apex for both the central and lateral incisors. 28 Similar to that reported by numerous authors, the bony dimensions demonstrated increment from the region of the alveolar crest to the level of the nasal spine. Males generally had a thicker bone in comparison to females; hence, females may require more precautions during implant insertion to avoid perforation of the NPC or buccal cortex, especially in the mid canal region.…”
Section: Morphology and Morphometry Of The Maxillary Bonesupporting
confidence: 86%
“…One study reported a significant difference in alveolar ridge thickness between the African Americans and Caucasians, with the former exhibiting thinner ridges at the apex for both the central and lateral incisors. 28 Similar to that reported by numerous authors, the bony dimensions demonstrated increment from the region of the alveolar crest to the level of the nasal spine. Males generally had a thicker bone in comparison to females; hence, females may require more precautions during implant insertion to avoid perforation of the NPC or buccal cortex, especially in the mid canal region.…”
Section: Morphology and Morphometry Of The Maxillary Bonesupporting
confidence: 86%
“…Equally important is the assessment of the adjacent anterior maxillary bone thickness. One study reported a signi cant difference in alveolar ridge thickness between the African Americans and Caucasians, with the former exhibiting thinner ridges at the apex for both the central and lateral incisors [21]. Similar to that reported by numerous authors, the bony dimensions demonstrated increment from the region of the alveolar crest to the level of the nasal spine.…”
Section: Morphology and Morphometry Of The Incisive Foramensupporting
confidence: 67%
“…The amount of information on the position of the upper incisors and their position in the alveolar bone continues to increase in the literature (1,11,(13)(14)(15)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Natomiast przechylanie lub cofanie zębów dolnych siecznych zmniejsza liczbę i zaawansowanie recesji od strony przedsionkowej nawet u osób z brakiem optymalnej higieny i obecnością stanu zapalnego przyzębia (10). W okolicy siekaczy kość wyrostka zębodołowego przedniego odcinka szczęki jest grubsza niż żuchwy, a kąty inklinacji siekaczy szczęki mają znaczną różnorodność jeszcze przed rozpoczęciem leczenia ortodontycznego, od klasycznie retruzyjnie ustawionych siekaczy górnych u pacjentów z II klasą podgrupą 2, do protruzyjnie ustawionych siekaczy w wyniku mechanizmu kompensacji zębowo-wyrostkowej u większości pacjentów III-klasowych (11,12).…”
Section: Badania Kliniczne / Clinical Researchunclassified
See 1 more Smart Citation